UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DENGAN MATERI SISTEM PEREDARAN DARAH MANUSIA MELALUI ALAT PERAGA ORGAN TUBUH DI KELAS V SDS KUSUMA BANGSA - Sarah Sohiah; Romi Ramdon Ginanjar; Sri Haryati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was conducted in class V of SDS Kusuma Bangsa II, semester one of the 2022/2023 school year with a total of 20 students. The research action was carried out using the demonstration method and physical organ teaching aids for science lessons. This research was conducted in two cycles. Based on the results obtained during the research, it can be explained that: The learning outcomes of class V students at SDS Kusuma Bangsa II are still far from the expected target. When studying science material on the human circulatory system, an average class score of 64 was obtained and of the 20 students, only 5 students got a minimum completion score of 75. The aim of the research was to determine the increase in student learning outcomes in learning science material on the human circulatory system through body organ props. The research was carried out through 4 stages including planning, implementing, observing and reflecting. The cycle was carried out 2 times the repair cycle. In cycle I on February 14 2023, the class average score in learning success and completeness reached 74.5 and cycle II on March 21 2023 achieved learning success and completeness with a class average score of 87. Based on the problems and research findings, The level of student learning outcomes in science learning material on the human circulatory system through the body organ teaching aid method in class V SDS Kusuma Bangsa II has increased after using simple visual aids made from used materials.